ANALYSIS OF THE EFFECT OF SCIENTIFIC LITERACY AND QUESTIONING ABILITY ON SCIENCE LEARNING OUTCOMES - Fitriana Syahwati; Syaiful Arif (INSECTA: Integrative Science Education and Teaching Activity Journal, 2022)
Achieving a learning purpose can be measured by learning participants. Learning results are the output of the learning process that learners produce from the learning activities that have been followed. These learning results relate to learners' ability and a supportive and far-reaching learning approach. So it is very important to know between components in the learning result. The scientific literacy approach and the ability to ask questions are key elements in improved learning. The study was intended to identify the impact between scientific literacy and the ability to inquire about the results of studying science at MTs Ngawi. The method of research used was the quantitative study method. The study population is MTS Ngawi with a study sample of 120 respondents from an ix class at kendal's MTS Al-Hidayah and MTsN 3 Ngawi. The study uses a question item test as an instrument for data collection that has been tested as a validity and religious one. The data obtained is analyzed with a quantitative description and statistics using linear mixed regression test analysis, anova, and coefficient determinations (R2). Based on the results of this study, it has been achieved that scientific literacy variables and the ability to ask affect simultaneously the results of studying science in 79% MTs with a regression of 62.824.